Pengenalan Investasi Saham dan Pengelolaan Risiko Bagi Mahasiswa Administrasi Bisnis - Leonardo Davidsi Sipayung; Eureka Try Zarazwanty R. Laega; Fahrian Arsyam Gultom; Zulfikar; M Novrizal Ramadhan (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Students’ interest in stock investment has increased alongside the growth of financial technology and easier access to capital markets. However, this interest is not fully supported by adequate understanding of investment risks and risk management strategies. This community service program aimed to improve Business Administration students’ understanding of stock investment and risk management as a basis for rational investment decision-making. The program was implemented through preparation, educational activities, and evaluation using an educative and participatory approach. The results show that although students initially had limited knowledge of investment risks, their understanding and perception of risk improved after the program. This activity contributes positively to enhancing students’ financial literacy in higher education.